Effectiveness of Virtual Reality Compared to Traditional Pronunciation Teaching Methods - Mushtariybegim Shomurodova Zarifovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This study investigates the effectiveness of virtual reality (VR) as a modern approach to pronunciation teaching in comparison with traditional methods. Pronunciation plays a vital role in language learning, requiring structured strategies to achieve accuracy in speech production. Traditional methods emphasize repetition drills, phonetic instruction, and teacher feedback, whereas VR provides immersive environments, real-time correction, and interactive simulations. The article explores the advantages and limitations of both approaches, supported by research evidence. It concludes that VR, when integrated with traditional methods, offers an innovative and effective approach to enhancing pronunciation skills.